Realising Indigenous Data Governance: A case study of the Koori Resource and Information Centre Archives - Shani Crumpen (Archives & Manuscripts, 2023)
This paper presents research findings from a study exploring how Indigenous community archives realise Indigenous Data Governance (ID-GOV). It considers the development of the Koori Resource and Information Centre (KRIC) Archives in Shepparton, Victoria, as a case study. This study aimed to determine whether the KRIC Archiving Project realised a form of ID-GOV. It adopted an Indigenous methodological framework using a combination of data collection methods to generate a range of research data. This study found that the KRIC Archiving Project adapted Western archival frameworks and practices to create an archive of local Indigenous significance and history that was accessed, operated and managed under Indigenous direction. In this way, the Project advanced Aboriginal and Torres Strait Islander self-determination and achieved a momentary emergence of ID-GOV.